The Reality of Agricultural Policies and Their Role in Achieving Sustainable Agricultural Development in Iraq - حسين محمد بدوي; بشير الكناني كامل كاظم; حسون رسول هادي (Journal of Economics and Administrative Sciences, 2020)
The Agricultural Policy is one of the most important tools adopted by the state to guide its economic and social activities through the delivery of suitable agricultural commodities to the consumer and in return to deliver agricultural inputs to the agricultural producers at the lowest possible cost to contribute in achieving a profit that helps the agricultural product to continue in the production process with the same efficiency and ambition. So as to help increase the contribution of the agricultural sector to GDP and achieve the best picture of sustainable agricultural development. The research aimed at identifying the reality of agricultural policies and their role in achieving sustainable agricultural development. The researcher found that there are a number of factors that hinder the application of agricultural policies in Iraq, foremost administrative and financial corruption. He also found that some agricultural departments of the Ministry of Agriculture, the agricultural product, has changed the direction of the impact on the production process, and concluded that most of the agricultural policies in Iraq are disabled and ineffective, they do not serve the agricultural product and the consumer and does not maintain the sustainability of natural resources is just ink on paper. At the end of the research, the researcher recommended a set of recommendations, including re-work on the agricultural initiative with not repeating the same mistakes and the work of serious meetings with riparian countries and leave shy meetings with them in the water crisis by making some suggestions satisfactory to all parties.